PENGARUH NILAI PELANGGAN, KOMUNIKASI DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PENGGUNA JASA TRANSPORTASI ONLINE GOJEK - Esih Jayanti; Ramadhani, Millenia Rizky; Werdiasih, Rustina Dewi (JURNAL EKONOMI, 2023)
This study aims to examine and analyze the Influence of Customer Value (X1), Communication (X2), Promotion (X3) to Customer Satisfaction (Y) on Gojek Online Transportasi Servise Users. Data was collected by distributing questionnaires to 120 Gojek Online Transportation Service Users. The sampling technique in this study used random sampling. The data analysis techniques used include validity test, reliability test, MSI test (Successive Interval Method), classical assumption test includes normality test, multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing includes t test and F test, coefficient analysis determination (R²). The results of the analysis show that the Customer Value has no effect to Customer Satisfaction on Gojek Online Transportation Servise Users with tcount < ttable (1.678 < 1.981) and significance value = 0.096 > 0.05. Communication has a positive effect to Customer Satisfaction on Gojek Online Transportation Servise Users with tcount > ttable (3.289 > 1.981) and significance value = 0.001 < 0.05. Promotion has no effect to Customer Satisfaction on Gojek Online Transportation Servise Users with tcount < ttable (-0,493 < 1.981) and significance value = 0.693 > 0.05. Customer Value, Communication and Promotion simultaneously have a positive effect to Customer Satisfaction on Gojek Online Transportation Servise Users with Fcount > Ftable (6.902 > 2.68) and significance value = 0.000 < 0.05.